TRADIȚIE ȘI MODERNISM ÎN EDUCAȚIE. PĂSTRAREA VALORILOR FUNDAMENTALE ALE EDUCAȚIEI PRIN PROMOVAREA LOR ÎN CONTEXTUL LUMII A TREIA (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2024)
Tradition and Modernism in Education. Preserving the Fundamental Values of Education by Promoting Them in the Third World  Context.Axiology1 is one of man’s indicators in the journey he undertakes to find the answers to the fundamental challenges of life. Considering the finite nature of earthly life, on the one hand, and the transcendence of the human being towards an infinite and heavenly life, on the other hand, man finds and faces, in his searching, a paradox, in that when the truth sought is finally defined, it is actually only the beginning of the journey, because the truth is not a  concept but a person, being of divine nature. Thus, thanks to this search – on  which in the end he will admit that it is still due exclusively to the divine  revelation – the man discovers other answers, and in the case of the present  article, the knowledge regarding the identity, the crisis and the restoration of  human being, the divine immanence and his supremacy over the all Creation,  becomes relevant through the quality of containing in itself the divine pathos  and praxis. This search finds its expression and materialization, in an obvious  nd expressive way, in the field of education, a field that will be addressed in  this article.